Cardiomyopathy related desmocollin-2 prodomain variants affect the intracellular cadherin transport and processing - Pohl, Greta Marie; Göz, Manuel; Gaertner, Anna; Brodehl, Andreas; Cimen, Tolga; Saguner, Ardan M.; Schulze-Bahr, Eric; Walhorn, Volker; Anselmetti, Dario; Milting, Hendrik (Frontiers in Cardiovascular Medicine, 2023)
Background Arrhythmogenic cardiomyopathy can be caused by genetic variants in desmosomal cadherins. Since cardiac desmosomal cadherins are crucial for cell-cell-adhesion, their correct localization at the plasma membrane is essential. Methods Nine desmocollin-2 variants at five positions from various public genetic databases (p.D30N, p.V52A/I, p.G77V/D/S, p.V79G, p.I96V/T) and three additional conserved positions (p.C32, p.C57, p.F71) within the prodomain were investigated in vitro using confocal microscopy. Model variants (p.C32A/S, p.V52G/L, p.C57A/S, p.F71Y/A/S, p.V79A/I/L, p.I96l/A) were generated to investigate the impact of specific amino acids. Results We revealed that all analyzed positions in the prodomain are critical for the intracellular transport. However, the variants p.D30N, p.V52A/I and p.I96V listed in genetic databases do not disturb the intracellular transport revealing that the loss of these canonical sequences may be compensated. Conclusion As disease-related homozygous truncating desmocollin-2 variants lacking the transmembrane domain are not localized at the plasma membrane, we predict that some of the investigated prodomain variants may be relevant in the context of arrhythmogenic cardiomyopathy due to disturbed intracellular transport.